PATHOGENETIC FACTORS OF CORONARY HEART DISEASE AND HELICOBACTER PYLORI INFECTION - O. N. Pavlov (Российский кардиологический журнал)
This literature review describes pathogenetic stages of chronic inflammation, as a factor associated with the development of atherosclerosis complications and coronary heart disease (CHD) progression. The author presents the evidence confirming atherogenic effects of Helicobacter pylori infection on the clinical course of CHD.